Genetically predicted blood metabolites mediate the association between immune cell characteristics and urolithiasis: A Mendelian randomization study and mediation analysis - Chengcheng Wei; Jiatai He; Jun Wen; Shunyao Wang; Mengjia Shi; Juan Hu; Huanhuan Tan; Jinjun Guo; Xiaosong Li (Genes and Diseases)
Urolithiasis, a disease characterized by the formation of urinary stones, is influenced by immune system dysregulation and metabolic factors. This study investigated the interplay between specific immune cell characteristics and blood metabolites in urolithiasis based on Mendelian randomization. We further explored the potential mediating effects of genetically predicted blood metabolites based on mediation analysis. We employed a two-sample Mendelian randomization analysis to examine the association between immune cell properties, blood metabolites, and urolithiasis risk. Genetic instruments for immune cell characteristics and blood metabolites were used to assess causal relationships and mediating pathways. Our results indicate that 10 immune cell characteristics had a unidirectional causal association with urolithiasis risk. We also detected 13 blood metabolites associated with urolithiasis. We identified 4 pathways through which genetically predicted blood metabolites partly mediated the association between specific immune cell characteristics and urolithiasis risk. This suggests potential mechanistic links where altered blood metabolites may play a role in developing urolithiasis through immune system modulation. This Mendelian randomization study highlights the complex relationship between immune responses, blood metabolites, and urolithiasis. The findings underscore the importance of considering both immune cell features and metabolic factors in understanding the pathogenesis of urolithiasis, offering insights into novel therapeutic targets and diagnostic strategies for this disorder.